Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
x^(log_10(x) + 2) = 1000?
Please include detail on how you got the solution (which I know is 10). Thanks.
X and x are the same variable, by the way; the first one got automatically capitalized.
4 Answers
- grunfeldLv 79 years agoFavorite Answer
x^( log x + 2 ) = 1000
(log x + 2 )log x = log 1000
(log x )^2 + 2 log x = 3
( log x )^2 + 2 log x - 3 = 0
( log x + 3 )(log x - 1 ) = 0
log x = - 3 or log x = 1
x = 1 / 1000 or 10
Source(s): my brain - Anonymous9 years ago
x^(log(x) +2) = x^(log(x)) * x²
1000 = 10³
so we have:
x^(log(x)) * x² = 10³
There is no analytical method for solving this equation, it must be done by inspection.
By definition: log_10(x) = y where 10^y = x
In this equation we have x^y * x² = 10³ so it would be really helpful if y =1
giving us x³ = 10³, from which x is clearly 10
well if x is 10, y actually does = 1:
log_10(10) = 1
It really is just by inspection, once you get used to using logs you'll start thinking of everything in terms of powers and the connections become more obvious
- maxineLv 45 years ago
Don't forget the exponent is subtracted when the former is split via the latter. Don't try to mislead others. In this case common factor is to be taken and then simplified. 2^one thousand - 2^999 = 2^999 (2 - 1) = 2^999 * 1 = 2^999
- s kLv 79 years ago
x^(log_{10}(x) + 2) = 1000
log_{10}(x^(log_{10}(x) + 2)) = log_{10}(10^3)
(log_{10}(x) + 2)•log_{10}(x) = 3
(ln(x)/ln(10) + 2)•ln(x)/ln(10) = 3
(ln(x) + 2•ln(10))•ln(x)/(ln(10)^2) = 3
ln(x)^2 + 2•ln(10)•ln(x) = 3•ln(10)^2
ln(x)^2 + 2•ln(10)•ln(x) - 3•ln(10)^2 = 0
ln(x)^2 - 1•ln(10)•ln(x) + 3•ln(10)•ln(x) - 3•ln(10)^2 = 0
ln(x)•(ln(x) - ln(10)) + 3•ln(10)•(ln(x) - ln(10)) = 0
(ln(x) - ln(10))(ln(x) + 3•ln(10)) = 0
=> ln(x) - ln(10) = 0, ln(x) = ln(10), e^ln(x) = e^ln(10), x = 10
=> ln(x) + 3•ln(10) = 0, ln(x) = -3•ln(10), ln(x) = ln(10^(-3)), e^ln(x) = e^ln(10^(-3)), x = 10^(-3)
So x ∈ {.001,10}.